The role of self-rated health in the association between chronic somatic diseases and climacteric-related symptoms - Katainen RE; Engblom JR; Siirtola TJ; Erkkola RU; Polo-Kantola P (TAYLOR & FRANCIS LTD, 2022)
Objectives: We have previously shown an association between several chronic somatic diseases and climacteric-related symptoms. This time, we investigated whether self-rated health (SRH) contributes to this association.Methods: The Women's Health Questionnaire was used to evaluate the climacteric-related symptoms, and existence of the diseases was investigated in 3421 women (41-54 years). In our previous study, the associations were defined with multivariable analyses. In the present study, SRH (good, moderate or bad) was included as a covariate.Results: Most of the previously found associations between the diseases and the symptoms lost their significance. Accordingly, SRH played an important role in the association between the diseases and the symptoms related to the climacteric.Conclusions: SRH seems to be of significant importance regarding the relationship between the chronic somatic diseases and the symptoms related to climacteric. Most of the diseases are not associated with the climacteric-related symptoms if the disease does not deteriorate the SRH. Thus, women's own perception of their health is crucial for their symptomatology.